Anti-Acne Effects of Cembrene Diterpenoids from the Cultured Soft Coral Sinularia flexibilis - Chen, Li-Wei; Chung, Hsuan-Lien; Wang, Ching-Chiung; Su, Jui-Hsin; Chen, Yu-Ju; Lee, Chia-Jung (Marine drugs, 2020)
Acne is a skin disease common in adolescents and increasingly common in the adult population. The major pathologic events of acne vulgaris include increased sebum production, retention hyperkeratosis, carrying commensal skin microbiota, and inflammation. In recent years, more than 10,000 compounds have been isolated and identified from marine organisms. The aim of this study was to discover the potential anti-acne activity of fraction 9 + 10 (SF-E) of Sinularia flexibilis extract and six cembrene diterpenoids. We found that the SF-E significantly reduced Cutibacterium acnes-induced edema in Wistar rat ears. The cembrene diterpenoids including 11-dehydrosinulariolide (SC-2), 3,4:8,11-bisepoxy-7-acetoxycembra-15(17)-en-1,12-olide (SC-7), and sinularin (SC-9) reduced nitric oxide (NO) production with 50% inhibitory concentration of 5.66 ± 0.19, 15.25 ± 0.25, and 3.85 ± 0.25 μM, respectively, and inducible NO synthase expression in RAW 264.7 cells. Moreover, treatment with SC-2, SC-7, and SC-9 significantly suppressed lipopolysaccharide- and heat-killed C. acnes-induced expression of proteins involved in mitogen-activated protein kinase pathway in both RAW 264.7 and HaCaT cells. After treatment with SC-2, SC-7, and SC-9, over-proliferation of HaCaT cells was significantly terminated. In summary, SC-2, SC-7, and SC-9 showed anti-inflammatory effects in RAW 264.7 cells, suggesting that these cembrene diterpenoids obtained from S. flexibilis are natural marine products with potential anti-acne activities.